Recent Trends of Bangladesh-India Relations: A Political Analysis - Siddiquei, Dr. Md. Riyad; Bhuiyan, Md. Ikhtiar Uddin (Asian Studies, 2023)
The political landscape of South Asia places a significant emphasis on the connection between Bangladesh and India. Both have a great deal in common, including commonalities in language, culture, history, and more. The two countries’ connection goes far beyond a strategic alliance. The purpose of this paper is to provide an analysis of the current interactions that have developed between Bangladesh and India. The widening trade deficit and the ongoing killing of Bangladeshis at the border are other major sources of concern. In 1975, India made the decision to construct the Farakka barrage, which is considered the beginning of the Ganga water dispute. They include India’s inability to take effective action on the equitable distribution of international river water, India’s partisan posture in the politics of Bangladesh, and India’s unwillingness to share fairly and with greater responsibility. This article sheds light on the uneven character of the connections between Bangladesh and India, as well as those between Bangladesh and other third-world countries. In terms of transit arrangements, Bangladesh is given exceptionally favorable pricing. With the signing of an agreement between Bangladesh and India concerning power, Bangladesh will be required to purchase electricity from India at a higher price. This will be the case going forward. It is possible to gain an understanding of the politics of South Asia by first becoming aware of the relationship between India, the most populous country in the region, and the other smaller countries in the region. In this paper, qualitative research method and secondary data have been used to address the research question.